Latin American anaphylaxis registry - Jares, Edgardo J. (2023)
Background: Recent data about clinical features, triggers and management of anaphylaxis in Latin America is lacking. Objective: To provide updated and extended data on anaphylaxis in this region. Method: An online questionnaire was used, with 67 allergy units involved from 12 Latin-American countries and Spain. Among data recorded, demographic information, clinical features, severity, triggering agents, and treatment were received. Results: Eight hundred and seventeen anaphylactic reactions were recorded. No difference in severity, regardless of pre-existing allergy or asthma history was found. Drug induced anaphylaxis (DIA) was most frequent (40.6%), followed by food induced anaphylaxis (FIA) (32.9%) and venom induced anaphylaxis (VIA) (12%). FIA and VIA were more common in children-adolescents. Non-steroidal anti-inflammatory drugs (NSAIDs) and beta-lactam antibiotics (BLA) were the most frequent drugs involved. Milk (61.1% of FIA) and egg (15.4% of FIA) in children, and shellfish (25.5% of FIA), fresh fruits (14.2% of FIA), and fish (11.3% of FIA) in adults were the most common FIA triggers. Fire ants were the most frequent insect triggers, and they induced more severe reactions than triggers of FIA and DIA (p < 0.0001). Epinephrine was used in 43.8% of anaphylaxis episodes. After Emergency Department treatment, epinephrine was prescribed to 13% of patients. Conclusions: Drugs (NSAIDs and BLA), foods (milk and egg in children and shellfish, fruits and fish in adults) and fire ants were the most common inducers of anaphylaxis. Epinephrine was used in less than half of the episodes emphasizing the urgent need to improve dissemination and implementation of anaphylaxis guidelines.